2017
DOI: 10.3892/etm.2017.4851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transoral endoscopic adenoidectomy on peripheral blood T-lymphocyte subsets in children with obstructive sleep apnea-hypopnea syndrome and its treatment strategy

Abstract: The objective of the present study was to investigate the effect of transoral endoscopic adenoidectomy on peripheral blood T lymphocyte subsets in pediatric patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) and its treatment strategy. Ninety-eight pediatric patients with adenoidal hypertrophy associated with OSAHS admitted to the Department of Otolaryngology, Xuzhou Children's Hospital were selected. After admission, patients received perfected 24 h polysomnogram monitoring, routine blood examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies have shown that cryogenic plasma‐assisted surgical treatment is more effective than traditional methods, with lower postoperative pain and no influence on patients' lung function and immune function 6,22–24 . Similarly, adenoidectomy is effective in patients with OSAHS, and transoral endoscopic adenoidectomy can also reduce mean arterial pressure and prolong nighttime sleep in patients with OSAHS 25–27 . In conclusion, cryogenic plasma‐assisted surgery has the advantages of minor trauma, less bleeding, faster recovery, and less postoperative pain than traditional surgery and therefore plays a vital role in surgical treatment 14…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have shown that cryogenic plasma‐assisted surgical treatment is more effective than traditional methods, with lower postoperative pain and no influence on patients' lung function and immune function 6,22–24 . Similarly, adenoidectomy is effective in patients with OSAHS, and transoral endoscopic adenoidectomy can also reduce mean arterial pressure and prolong nighttime sleep in patients with OSAHS 25–27 . In conclusion, cryogenic plasma‐assisted surgery has the advantages of minor trauma, less bleeding, faster recovery, and less postoperative pain than traditional surgery and therefore plays a vital role in surgical treatment 14…”
Section: Discussionmentioning
confidence: 97%
“…6,[22][23][24] Similarly, adenoidectomy is effective in patients with OSAHS, and transoral endoscopic adenoidectomy can also reduce mean arterial pressure and prolong nighttime sleep in patients with OSAHS. [25][26][27] In conclusion, cryogenic plasmaassisted surgery has the advantages of minor trauma, less bleeding, faster recovery, and less postoperative pain than traditional surgery and therefore plays a vital role in surgical treatment. 14 This study systematically evaluated the effectiveness and safety of cryo-plasma tonsillectomy for OSAHS.…”
Section: Discussionmentioning
confidence: 98%
“…Adenoidectomy is another widely used method in treatment of OSAHS. Yang et al reported that transoral endoscopic adenoidectomy decreased the mean arterial pressure and increased the duration of nocturnal sleep of OSAHS patients [ 30 ]. In another study, Ding et al demonstrated that a combination of adenoidectomy, tonsillectomy, and soft palate-pharyngoplasty was effective to enlarge the anteroposterior diameter and transverse diameter of the isthmus faucium to achieve better efficacy in OSAHS patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Reduction in tumor necrosis factor-α (TNG-α), proinflammatory cytokine, and increased CD4+/CD8+ T lymphocyte ratio after adenotonsillectomy was also reported. 22,23) However, most of the studies on growth, symptom and laboratory changes after tonsillectomy included small number of patients and short-term follow-up periods, and there have been few studies on long-term effects on growth or symptom changes.…”
Section: Discussionmentioning
confidence: 99%